2016
DOI: 10.2147/ijwh.s118687
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness evaluation comparing originator follitropin alfa to the biosimilar for the treatment of infertility

Abstract: ObjectivesTo perform a cost-effectiveness evaluation comparing the originator follitropin alfa (Gonal-f®) to the biosimilar (Bemfola®) in the Italian and Spanish contexts, with an assessment of the German and UK backgrounds.MethodsStarting from the study by Rettenbacher et al, a cost-effectiveness model was developed in the Italian and Spanish contexts. Clinical data on subjects, doses of gonadotropin, pregnancies, live-born children, and ovarian hyperstimulation syndrome were used to feed the model. Costs rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
1
9
2
Order By: Relevance
“…However, assuming similar effectiveness between corifollitropin alfa and rFSH is supported by other studies ( Devroey et al, 2009 , Obruca et al, 2010 ) and recent meta-analyses ( Fensore et al, 2015 , Griesinger et al, 2016 , Pouwer et al, 2016 ). As regards comparing similar effectiveness between different rFSH, Gizzo et al (2016) considered follitropin alfa biosimilar_B to be less effective than follitropin alfa, which is in contrast to the findings of this study.…”
Section: Discussioncontrasting
confidence: 99%
“…However, assuming similar effectiveness between corifollitropin alfa and rFSH is supported by other studies ( Devroey et al, 2009 , Obruca et al, 2010 ) and recent meta-analyses ( Fensore et al, 2015 , Griesinger et al, 2016 , Pouwer et al, 2016 ). As regards comparing similar effectiveness between different rFSH, Gizzo et al (2016) considered follitropin alfa biosimilar_B to be less effective than follitropin alfa, which is in contrast to the findings of this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Gizzo et al (2016) estimated the cost-effectiveness of the Originator compared to Biosimilar 1 over two treatment cycles in Italy and Spain. The cost per live birth was also estimated to be lower for Originator in Italy and Spain, €7,044 and €12,283 respectively, compared to €7,411 and €13,494 for Biosimilar 1 23. Like the analysis presented in the current study, the analyses by Silverio et al (2015) and Gizzo et al (2016) were based on clinical evidence reported by Rettenbacher et al14.…”
Section: Discussionmentioning
confidence: 50%
“…A cost-effectiveness evaluation comparing the originator follitropin α Gonal-F ® to the biosimilar Bemfola ® , based on data derived from the registration study by Rettenbacher [ 65 ], established that the originator r-hFSH is more cost-efficient than the biosimilar relative to the conditions of medical reimbursement existing in Italian and Spanish health systems. All clinical data and the costs of the procedure, including the overall r-hFSH dose and the costs related to drugs, hospitalizations and examinations were taken into account and related to the number of live births; compared to the originator, the biosimilar generated an higher cost of € 3600 for Italy and € 900 for Spain [ 70 ].…”
Section: Cost-effectiveness Evaluation Of Follitropin α mentioning
confidence: 99%